The danger of a one-sided story: The effects of production regimes and family policies on the gender employment gap - Ji Young Kang (Luxembourg Income Study (LIS), 2017)
Despite growing interest in the effects of variations in work and family reconciliation policies on female employment across countries, the questions in what way and to what extent production regimes influence female employment provide an important backdrop to the current research. Drawing on Varieties of Capitalism (VoC) literature, I examine the effects of production regimes and work and family reconciliation policies on the gender employment gap simultaneously in 15 Organization for Economic Co-operation and Development (OECD) countries using the Luxembourg Income Study (LIS). Childcare is associated with a lesser degree of gender gap in employment participation and leave generosity has a curvilinear relation with the gender employment gap. Whereas the coordinated market economies themselves are associated with smaller gender gaps in employment participation, in the coordinated market economies leave generosity produces a higher gender employment gap than in the liberal market economies. This research highlights the importance of production regimes in understanding female employment and the interactive effects of leave generosity by production regimes.
Keywords: 330; Gender employment gap; Varieties of Capitalism (VoC); production regimes; work and family reconciliation policies (leave generosity; public childcare)